Religion and Civil Society in the Arab World: In the Vortex of Globalization and Tradition - Haddad, Tania (Ethics, Human Rights and Global Political Thought Ser, 2018)
Cover -- Title -- Copyright -- Dedication -- CONTENTS -- List of contributors -- Acknowledgments -- Introduction: changing role of civil society in the Arab world -- PART I Sacred/non-secular perspectives on civil society and politics in the Arab world -- 1 Disambiguating the idea of public sphere and secularism in the Middle East -- 2 Civil society and non-profit governance in the Arab world -- 3 Rethinking Arab civil society: Arab Revolutions and reconceptualization of civil society -- 4 The changing role of Arab civil society: between fundamentalism and civic activism -- PART II Significant case studies -- 5 Trapped in a vicious circle? Why Egyptian civil society failed to capitalize on the revolution -- 6 Civil society and political transition: the cases of Tunisia and Libya -- 7 Religion, relief and reform: the history of civil society in Lebanon -- 8 Constraints on Lebanese nongovernmental organizations: a survey of the literature -- Conclusion